Dampak Pandemi COVID-19 terhadap Capaian Sustainable Development Goals (SDGs): The Impact of the COVID-19 Pandemic on the Achievement of Sustainable Development Goals [SDGs] - Muhammad Habibi; Dyah Anugrah Pratama (JOURNAL OF GOVERNMENT SCIENCE, 2021)
This study aims to analyze the impact of COVID-19 on the achievement of the Sustainable Development Goals (SDGs) in Indonesia. The sustainable development goals represent a global plan of action, approved by world leaders, intended to end poverty, reduce social inequality, and protect environment. These SDGs consist of 17 goals and 169 targets that are scheduled to be achieved by 2030, and Indonesia began implementing them in 2015. The method used in this study was a bibliometric and descriptive evaluative analysis, wherein data was collected by using the Publish or Perish application, and then processed with VOSviewer application software. Four indicators needed to be scrutinized, namely; (1) the socio-economic impact of COVID-19; (2) the impact of COVID-19 on sustainable development goals; (3) the new normal for the achievement of the SDGs; and (4) the financing of SDGs in a post-COVID period. The results of the study show that the socio-economic impact of the COVID-19 pandemic greatly influences SGDs. Cost is a crucial factor as pandemic’s cost is huge, and by all means has a direct impact on SGD efforts. To realize SGDs by 2030 would require governments around the world to improvise in dealing with it, and indeed implement a new normal in governance processes.